The dual role of extracellular vesicles derived from animal and human immune cells: A systematic review. (Journal of Advanced Veterinary and Animal Research, 2025)
This review aims to examine the functions of extracellular vesicles (EVs) originating from animal and human immune cells, with a focus on their roles in immunomodulation and therapeutic potential. It highlights their dual effects in infection and autoimmunity, cancer treatment, inflammatory conditions, and regenerative medicine while also addressing the challenges in standardizing EV production, isolation, and characterization for clinical applications. This review highlights the need for robust protocols to advance EV-based therapies. It also synthesizes current literature on immune cell-derived EVs, with a focus on their mechanisms of action in intercellular communication, immune modulation, and therapeutic delivery. Additionally, it examines studies that explore the regenerative potential of immune cell-derived EVs and discusses the technical and methodological challenges involved in EV research and clinical translation. EVs from immune cells can either boost or reduce immune responses in tumor therapy, which greatly affects how cancer develops and how well treatments work. These EVs also show promise in managing inflammatory diseases through immune modulation and targeted therapeutic delivery. Furthermore, immune cell-derived EVs possess regenerative properties, contributing to tissue repair and the maintenance of homeostasis. Despite these promising roles, challenges related to the standardization of EV production, isolation, and characterization continue to impede clinical translation, for improved protocols to ensure reproducibility and scalability. Immune cell-derived EVs possess substantial therapeutic potential in cancer treatment, inflammatory diseases, and regenerative medicine. These tiny membrane-bound particles, naturally released by immune cells, carry bioactive molecules that can modulate immune responses, suppress tumor growth, or promote tissue repair. However, before these therapies can be widely used in clinics, key challenges must be addressed, particularly in standardizing their production, characterization, and quality control.J. Adv. Vet. Anim. Res., 12(2): 497–515, June 2025http://doi.org/10.5455/javar.2025.l915